(untitled) (Economic Journal of Nepal, 2025)
The paper mainly analyzed the trend and examined the role of agricultural foreign aid on agricultural GDP of Nepal. Although agricultural sector is taken as the backbone of Nepalese economy, its productivity is not at satisfactory level. Unless and until the market-oriented commercial farming and diversification of agriculture are initiated, the production and productivity of agriculture will not increase. But due to low national saving, it is possible only through foreign aids. Nepal started receiving foreign aid officially since 1951 from USA. The study used secondary data covering 19 years from the FY 1996/1997 AD to 2014/2015 AD. It is an analytical study using deductive method, coefficient of determinants, ARDL approach, ADF unit-root test, LM test, heteroscedasticity, Jarque-Bera statistics, and CUSUM test for short and long run effects of independent variables to the dependent variable. The study concluded that both real agricultural foreign aid and real agricultural GDP are fluctuating and the contribution of agricultural sector to GDP has continued to decline. Similarly, there is a positive impact of agricultural foreign aid on agricultural GDP. There is long run co integration between real agricultural foreign aid and real agricultural GDP. Therefore, the government of Nepal should focus on effective use of foreign aid in agricultural development.